2022
DOI: 10.3389/fimmu.2022.939464
|View full text |Cite
|
Sign up to set email alerts
|

Immunoprotective Effects of Two Histone H2A Variants in the Grass Carp Against Flavobacterium columnare Infection

Abstract: In teleost fish, the nucleotide polymorphisms of histone H2A significantly affect the resistance or susceptibility of zebrafish to Edwardsiella piscicida infection. Whether histone H2A variants can enhance the resistance of grass carp to Flavobacterium columnare infection remains unclear. Here, the effects of 7 previously obtained variants (gcH2A-1~gcH2A-7) and 5 novel histone H2A variants (gcH2A-11, gcH2A-13~gcH2A-16) in response to F. columnare infection were investigated. It was found that these histone H2A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
(57 reference statements)
0
0
0
Order By: Relevance
“…Research indicates that the complete histone H2A of zebrafish possessed antimicrobial properties against the Gram-negative bacterium Edwardsiella piscicida in vivo, though its efficacy was somewhat constrained [42]. Nonetheless, it has been discovered that histone variants and histone-derivative peptides, because of their structural changes and sequence modifications, exhibit enhanced antibacterial properties [43][44][45]. Lectin families, which include RegIIIalpha and RegIIIgamma, feature prominently in the enriched pathways.…”
Section: Classification and Significance Of Amps In Teleostsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research indicates that the complete histone H2A of zebrafish possessed antimicrobial properties against the Gram-negative bacterium Edwardsiella piscicida in vivo, though its efficacy was somewhat constrained [42]. Nonetheless, it has been discovered that histone variants and histone-derivative peptides, because of their structural changes and sequence modifications, exhibit enhanced antibacterial properties [43][44][45]. Lectin families, which include RegIIIalpha and RegIIIgamma, feature prominently in the enriched pathways.…”
Section: Classification and Significance Of Amps In Teleostsmentioning
confidence: 99%
“…This might have indicated that, under certain conditions, they participated in biological processes through mutual interactions and, in specific splice forms, were activated. Through various cascading signal transductions, they activated downstream factors, achieving antimicrobial efficacy [45,51,52].…”
Section: Ppi Analysis and Covariance Analysis Of Ampsmentioning
confidence: 99%